Facial muscle activations by functional electrical stimulation. (February 2019) - Ilves, Mirja; Lylykangas, Jani; Rantanen, Ville; Mäkelä, Eeva; Vehkaoja, Antti; Verho, Jarmo; Lekkala, Jukka; Rautiainen, Markus; Surakka, Veikko
Highlights: Transcutaneous facial muscle stimulations of healthy participants (N=24) were investigated. Visually observable movement of the forehead and the lower lip was achieved in all participants. Stimulation of a smile was more challenging. Stimulations evoking small movements were rated as relatively pleasant and tolerable. Complete eye blink was achieved in 22 participants, and the sensation was rated mainly as tolerable. The results encourage developing further facial pacing technology, which can offer a new treatment option for patients with facial paralysis. Abstract: The present aim was to investigate transcutaneous facial muscle stimulation in order to take further steps in developing facial pacing technology, which can offer a new treatment option for patients with unilateral facial paralysis. This technology ultimately measures muscle activations from one side of the face and simultaneously activates the corresponding muscles of the other side with electrical stimulation. Four facial muscle locations— frontalis, orbicularis oculi, zygomaticus major, and orbicularis oris —of the healthy participants (N = 24) were stimulated to produce an eyebrow raise, eye blink, smile, and lip pucker, respectively. The results showed that a visually observable movement of the forehead and the lower lip was achieved in all participants. On average, the stimulations at the movement threshold were rated as tolerable in terms of pain ratings and neutral in terms of pleasantness ratings. Complete eye blink was achieved in 22 participants, and most did not experience painful sensations. The stimulation of the cheek evoked observable movement in 23 participants, but the stimulation also often resulted in concurrent activation of the eye, mouth, and nose area. The results suggest that transcutaneous stimulation seems to be a promising method for developing further facial pacing technology.